INCIDENCE OF RECURRENT LARYNGEAL NERVE PALSY IN CERVICAL ANASTOMOSIS AFTER ESOPHAGECTOMY FOR CARCINOMA ESOPHAGUS - Hussain, Zahid; Majeed, Farhan Ahmed; Raza, Maqbool; Shahbaz, Aaisha; Rafique, Atif; Farhan, Nabeela (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study the incidence of Recurrent Laryngeal Nerve Palsy (RLNP) in cervical anastomosis after esophagectomy for carcinoma of the esophagus.Study Design: Prospective observational study.Place and Duration of Study: Military Hospital’s Thoracic surgery departments, Combined Military Hospital Rawalpindi, Combined Military Hospital Lahore and Combined Military Hospital Multan, from Jan 2010 to Sep 2020.Methodology: Designated proformas were used to collect data. Histopathologically proven, operable cases of carcinoma esophagus with normal phonation were included, all of which underwent cervical anastomosis. All cases of benign pathologies and per-operative macroscopically advanced loco-regional disease were excluded. Recurrent laryngeal nerve (RLN) was identified in all cases and follow-up of 6 months for recovery period was executed.Results: 220 cases were included out of which 121 (55%) were males while 99 (45%) females. The age range was 14-81 years (mean is 38.7 ± 16.78). Out of 29 (13.6%) cases underwent minimally invasive esophagectomy (MIE) while thoracophreno laparotomy was performed in 100 (45.4%) cases, McKeown in 46 (20.9%) and Trans-hiatal esophagectomy (THE) in 45 (20.4%) patients. Recurrent Laryngeal Nerve Palsy was found in 19 patients (8.6%), tracheal injury in 3 (1.3%) and bronchial injury in 1 (0.4%) patient. Recurrent Laryngeal Nerve Palsy was transient in 14 cases and permanent damage persisted in 5 patients.Conclusion: Recurrent Laryngeal Nerve Palsy after esophagectomy is related to increased morbidity due to respiratory complications. With Sharp dissection technique, adequate surgical skill and equipment, the incidence of Recurrent Laryngeal Nerve Palsy can be decreased. In our study, it is less............